Teachers of the Jesuit College of Kražiai, 1616–1773: Teaching Experience in Jesuits‘ Biographies - Balčiūnaitė, Brigita (Senoji Lietuvos literatūra, 2017)
The article takes a look at the teaching personnel of the Jesuit College of Kražiai. In the first part, it discusses the curriculum of Kražiai College (existed from 1616 to 1773) and its peculiarities. In the second part, focus is placed on the teaching community of Kražiai College, more precisely, on the teachers’ origins, teaching practice, and their further careers. Biographies of the Jesuits reveal that for some of them teaching was just one of many steps in Jesuitical formation, a temporary occupation, while others dedicated their entire life to teaching. Jesuits were often assigned to teaching positions only after completing the novitiate, that is, two years after joining the Order, and they taught different disciplines. There also existed another model: a Jesuit began lecturing after finishing three years of philosophy studies, that is, five years after joining the Order. The biographies of the college teachers reveal that, in addition to the fact that Kražiai College followed the general standard, the college and its teaching personnel had some specific features. Based on the Jesuits’ biographies, we can also see that some exceptional teaching situations resulted from shortages of teaching personnel, but they also reflected exceptional personal abilities.